ANALISIS NUMERIK DISTRIBUSI TEKANAN & KECEPATAN ALIRAN UDARA PADA FUSELAGE B737-9 MAX - Tri Susilo; Bismil Rabeta; Fikry Falah (Jurnal Teknologi Kedirgantaraan, 2019)
Aerodynamic characteristics can be known by using computational Fluid Dynamics(CFD) methods. This study analyzes the pressure distribution andvelocity of air flow on FuselageB737-9 MAX using the Computational Fluid Dynamics (CFD) method with variations in attackangles of 0o, 15o, 30oand 45o. The results obtained are at 0oattack angle, 15othe difference inspeed and pressure is not too significant or normal, while at the attack angle 30oand 45othedifference in speed and pressure is very significant or abnormal because the air flow at that angleexperiences turbulence around the fuselage.